Authority of Procurement and Maintenance of Traffic Facilities and Infrastructure on National Roads - Gandung Triyanto; Aidul Fitriciada Azhari; Wardah Yuspin (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
Law 32 of 2004, regional autonomy, mandates the improvement of community services and regional equity by encouraging community participation. Meanwhile, Law 22 of 2009 on road traffic and transportation mandates the maintenance of traffic infrastructure, particularly The Road Traffic Signaling Devices (APILL) on National Roads, National with Provincial Roads intersection, and National with Regency/City Roads intersection to BPTD–The representative of the Ministry of Transportation. In practice, all maintenances are by Regency/City Transportation Service, including the maintenance of the Traffic Signaling Device (APILL) at National and Provincial Roads intersection with Regency/City Roads. The study aims to evaluate Law 22/2009 and its implementing regulations. Besides, This study also attempts to determine the implementation of Traffic Signaling Devices (APILL), including its procurement and maintenance. The research method was legal research. It involved investigating related regulations to the problem under study. The study concludes the maintenance implementation of traffic signaling devices (APILL) is the best fit for the Regency/City Transportation Service. In addition, it is necessary to revise the governing rules for maintaining traffic infrastructure, the traffic signaling devices (APILL).